Cerebral cortex layer segmentation using diffusion magnetic resonance imaging in vivo with applications to laminar connections and working memory analysis. Issue 17 (1st July 2022) - Zhang, Jie; Sun, Zhe; Duan, Feng; Shi, Liang; Zhang, Yu; Solé‐Casals, Jordi; Caiafa, Cesar F.
Abstract: Understanding the laminar brain structure is of great help in further developing our knowledge of the functions of the brain. However, since most layer segmentation methods are invasive, it is difficult to apply them to the human brain in vivo. To systematically explore the human brain's laminar structure noninvasively, the K‐means clustering algorithm was used to automatically segment the left hemisphere into two layers, the superficial and deep layers, using a 7 Tesla (T) diffusion magnetic resonance imaging (dMRI)open dataset. The obtained layer thickness was then compared with the layer thickness of the BigBrain reference dataset, which segmented the neocortex into six layers based on the von Economo atlas. The results show a significant correlation not only between our automatically segmented superficial layer thickness and the thickness of layers 1–3 from the reference histological data, but also between our automatically segmented deep layer thickness and the thickness of layers 4–6 from the reference histological data. Second, we constructed the laminar connections between two pairs of unidirectional connected regions, which is consistent with prior research. Finally, we conducted the laminar analysis of the working memory, which was challenging to do in the past, and explained the conclusions of the functional analysis. Our work successfully demonstrates that it is possible to segment the human cortex noninvasively into layers using dMRI data and further explores the mechanisms of the human brain. Abstract : This manuscript contains two main results: (a) First, it proposes a K‐means clustering algorithm to automatically segment the left hemisphere into two layers, on a 7 Tesla diffusion magnetic resonance imaging (MRI) data. The results demonstrate that the cerebral cortex can be successfully divided into the superficial and deep layers, corresponding to layers 1–3 and 4–6 of the Brodmann atlas, respectively. (b) Second, two pairs of unidirectional connected regions were selected to validate the laminar connections. The results show that estimating laminar connections using diffusion MRI (dMRI) is valuable and it indicates that dMRI has the potential to estimate laminar connections. The method was used to analyse the working memory, which was challenging to do in the past.